The Problem of Energy Security in the Early 21st Century: Challenges and Opportunities - A. V. Dedenkulov (Vestnik MGIMO-Universiteta)
The article analyses the present-day specifics of energy security and its potential impact on international relations. Generalizing the global energy forecasts up to 2030-2035 the author singles out “points of tenderness”, the elements of global energy security fraught with tension in the years to come. The article emphasizes the urgent need of the current developments in the global “energy landscape” to be considered in the framework of the Russian foreign policy.